PENGARUH ELECTRONIC WORD OF MOUTH DAN KUALITAS WEBSITE TERHADAP MINAT BELI KONSUMEN PADA MOBIL TOYOTA CALYA DI WILAYAH TANGERANG SELATAN - Ari Firmansyah; Budi Permana Yusuf; Edi Setiawam (Program Studi Manajemen Fakultas Ekonomi UST, 2021)
This study aims to determine the effect of Electronic Word of Mouth and the quality of the website on consumer buying interest. Data retrieved by questionnaire from 100 respondents South Tangerang people who know or are interested in the Toyota Calya. The data were processed using regression analysis using IBM SPSS Statistics 25. The results of the research Electronic Word of Mouth to express interest in buying Electronic Word of Mouth is partially significant and positive impact on buying interest. In addition, the study found that the quality of the website and a significant positive effect on consumer buying interest. The results of the simultaneous test also declare a variable Electronic Word of Mouth and a website Quality significant and positive impact on consumer buying interest. things can be seen from the results Fcounts 140.567 value greater than the value of Fcounts > Ftable (2,98) = 140.567> 3.09, and the significance value 0.000 <0.05, which means that the variable Electronic Word of Mouth and the quality of the website together or simultaneously have a significant influence on consumer buying interest. These results indicate if the Electronic Word of Mouth and the quality of the website can increase consumer buying interest.